Clinical Outcomes of Single vs. Two-Strain Probiotic Prophylaxis for Prevention of Necrotizing Enterocolitis in Preterm Infants - Archana Priyadarshi; Archana Priyadarshi; Gemma Lowe; Vishal Saddi; Amit Trivedi; Melissa Luig; Mark Tracy (Frontiers Media S.A., 2021)
Background: The administration of live microbiota (probiotic) via enteral route to preterm infants facilitates intestinal colonization with beneficial bacteria, resulting in competitive inhibition of the growth of pathogenic bacteria preventing gut microbiome dysbiosis. This dysbiosis is linked to the pathogenesis of necrotizing enterocolitis (NEC), an acquired multi-factorial intestinal disease characterized by microbial invasion of the gut mucosa, particularly affecting preterm infants. Probiotic prophylaxis reduces NEC; however, variations in strain-specific probiotic effects, differences in administration protocols, and synergistic interactions with the use of combination strains have all led to challenges in selecting the optimal probiotic for clinical use.Aim: To compare any differences in NEC rates, feeding outcomes, co-morbidities in preterm infants receiving single or two-strain probiotics over a 4-year period. The two-strain probiotic prophylaxis was sequentially switched over after 2 years to the single strain probiotic within this 4-year study period, in similar cohort of preterm infants.Methods: During two consecutive equal 2-year epochs, preterm infants (<32 weeks and or with birth weight <1,500 g) receiving two-strain (Lactobacillus acidophilus and Bifidobacterium bifidum) and single strain (Bifidobacterium breve M-16 V,) probiotic prophylaxis for prevention of NEC were included in this retrospective, observational study. The primary outcome included rates of NEC; secondary outcomes included prematurity related co-morbidities and feeding outcomes. Time to reach full enteral feeds was identified as the first day of introducing milk feeds at 150 ml/kg/day.Results: There were 180 preterm infants in the two-strain, 196 in the single strain group from the two equal consecutive 2-year epochs. There were no differences in the NEC rates, feeding outcomes, all-cause morbidities except for differences in rates of retinopathy of prematurity.Conclusion: In our intensive-care setting, clinical outcomes of single vs. two-strain probiotic prophylaxis for prevention of NEC were similar. Although our study demonstrates single strain probiotic may be equally effective than two-strain in the prevention of NEC, small sample size and low baseline incidence of NEC in our unit were not sufficiently powered to compare single vs. two-strain probiotic prophylaxis in preventing NEC. Further clustered randomized controlled trials are required to study the effects of single vs. multi-strain probiotic products for NEC prevention in preterm infants.